Existence and asymptotic behavior of solutions to a quasi-linear hyperbolic-parabolic model of vasculogenesis - Di Russo, Cristiana; Sepe, Alice (SIAM journal on mathematical analysis, 2013)
We consider a hyperbolic-parabolic model of vasculogenesis in the multidimensional case. For this system we show the global existence of smooth solutions to the Cauchy problem, using suitable energy estimates. Since this model does not enter in the classical framework of dissipative problems, we analyze it combining the features of the hyperbolic and the parabolic parts. Moreover we study the asymptotic behavior of those solutions showing their decay rates by means of detailed analysis of the Green function for the linearized problem.
Gesehen am 15.12.2020